Wave Dissipation and Mean Circulation on a Shore Platform Under Storm Wave Conditions. Issue 3 (7th March 2022) - Lavaud, Laura; Bertin, Xavier; Martins, Kévin; Pezerat, Marc; Coulombier, Thibault; Dausse, Denis
Abstract: While wave processes on shore platforms have been recently advanced by a number of field‐based studies, few attention has been paid to the role of bed roughness on wave dissipation and wave setup dynamics in these environments. This study reports on a new field experiment conducted under storm wave conditions on a gently sloping shore platform which was instrumented from 10 m water depth up to the shoreline. Data analyses are complemented with numerical simulations performed with a 3D fully coupled modeling system using a vortex force formalism to represent the effects of short waves on the mean circulation. An accurate representation of wave dissipation by both depth‐induced breaking and bottom friction is found essential to reproduce the transformation of short waves across the platform and the resulting wave setup. Wave energy dissipation by bottom friction is dominant in the subtidal part of the platform and contributes to about 40% of the total wave energy dissipation. The enhanced wave bottom friction on the platform decreases the wave height before breaking, which reduces the contribution of wave forces to the wave setup compared to a smooth bottom (mechanism 1). Conversely, an idealized analysis of the cross‐shore momentum balance reveals that the wave‐induced circulation increases the wave setup, this process being enhanced on a rough bottom (mechanism 2). The contribution of mechanism 2 increases with the bottom slope, accounting for up to 26% of the wave setup for a 1:20 sloping shore platform, and overcoming mechanism 1. Plain Language Summary: In the nearshore, the dissipation of short waves controls the mean circulation by generating currents but also a rise of the mean water level along the shoreline, a process known as the wave setup. Waves and wave‐induced processes on shore platforms can be different from that on sandy beaches, principally due to a higher bed roughness. This study reports on a new field experiment conducted under storm wave conditions (short waves reaching 6 m at 50 m depth) on a gently sloping shore platform which was instrumented from 10 m water depth up to the shoreline. Data analyses are complemented with numerical simulations performed with a three‐dimensional modeling system coupling a wave and circulation models. The results show that wave bottom friction occurring on the platform explains 40% of the total wave energy dissipation, which reduces the contribution of wave dissipation to the wave setup (mechanism 1). Conversely, further analysis reveals that depth‐varying currents forced by waves increase the wave setup, the rough bottom making this mechanism stronger (mechanism 2). Mechanism 2 counteracts mechanism 1 and becomes even dominant as the bottom slope increases, accounting for up to 26% of the wave setup for a 1:20 sloping shore platform. Key Points: A new field data set collected during storm wave conditions on a shore platform instrumented from 10 m water depth up to the shoreline Wave bottom friction explains about 40% of the total wave energy dissipation across the shore platform and reduces the wave setup The contribution of the wave‐induced circulation to the wave setup is enhanced on the rough bottom and increases with the bed slope